Telephone and time management : making it a tool and not a tyrant - Scott, Dru (Crisp Pub. Menlo ParkUS, 1988)
Provides five strategies for reaching target calls; and strategies for dealing with telephone interruptions. Advises on aspects of telephone etiquette including: proper use of names; taking messages; and terminating calls. Suggests friendly wordings to replace expressions which impact negatively e.g. 'You have to call...' is replaced by 'Will you call...?'